Analysis of Competitiveness and Determinant of Seaweed Export Value (Hs 121221) Indonesia to Export Destination in 2012-2018 Period - Henidar, Novida; Firmansyah, Firmansyah (AFEBI Economic and Finance Review, 2020)
The study was examined of Indonesian export of seaweed commodity (HS 121221) in 13 main export destination country (China, Korea, Vietnam, Chilli, Hong Kong, France, Spain, the Philippines, Denmark, Japan, Malaysia, Tunisia, and the United States) by using method of RCA (Revealed Comparative Advantage) index and EPD (Export Product Dynamics) index, and factors affecting the export of Indonesian seaweed to the main export destinations for 2012-2018. The Panel data regression method with a fixed-effect model is used to analyze the export model from the demand and supply side. The results showed that within 7 years period (2012-2018), RCA (Revealed Comparative Advantage), trade openness, and GDP had a positive and significant effect while LCU (Local Currency Unit), Consumer Price Index (CPI), and seaweed prices international influence negatively and significantly.